OPTIMIZATION OF THE AUTHORITY OF THE NATIONAL HAM COMMISSION IN FULFILLING HUMAN RIGHTS IN INDONESIA - Berutu, Riski Pardinata; Darmawansyah Sihombing, Rizky; Sharfina Desiandri, Yati (NOMOI Law Review, 2024)
Problems related to Human Rights still often occur in Indonesia. Based on historical records, gross human rights violations occurred during the New Order government. The many human rights violations that occurred have not been resolved until now. In fact, in terms of authority, Komnas HAM is given the authority to conduct investigations into allegations of gross human rights violations. Not only that, the functions and duties of Komnas HAM can also be concluded as preventive duties and functions so that human rights violations do not occur. However, the authority of these duties and functions has not been optimally implemented by Komnas HAM. This can be seen from the conflict related to allegations of gross human rights violations in the past that have not been resolved. This research is a normative legal research with a statute approach. In the end, it can be seen that the existence of Komnas HAM began in 1993 through Keppers No. 50 of 1993 which has developed and regulated Komnas HAM into Law No. 39 of 1999 concerning human rights. Normatively, Komnas HAM has the function of studying, researching, providing information, monitoring, and mediating human rights. However, this function is considered not to have been implemented optimally considering the many human rights violations that still occur in the community.